Dealing with “Dhimmi’s” Jews & Christians in the Umayyad Period - Nasiri, Imad Tali Mahdi Al (International Journal of Psychosocial Rehabilitation, 2020)
It can be said that the lack of historical information related to the “Dhimmi’s” has cast a shadow on Arab researchers and made them move away from delving into such topics that we can classify in the fields of social studies that already suffer from a clear lack and reluctance of many researchers and historians who focused most of their attention on studying political aspects without other.The history of Islam is a testimony that Muslims did not hate anyone in any era of history from abandoning their religion. Islam is a religion of reason and common sense, and no one is forced to enter it compulsively. He challenged the first and the others with his immortal miracle. others, or that they forced anyone from any of the Jewish or Christian sects to convert to Islam